The art of teaching science in secondary schools: A meta analysis - Syed Hassan, Sharifah Sariah; Ibrahim, Ahmad Abdullahi (Turkish Online Journal of Educational Technology, 2018)
This study attempts to highlight the trend of research in science related subjects specifically in schools. Articles and journals were retrieved from Google scholar under peer reviewed with the aim to highlight the trend of research methods, findings and teaching strategies. The themes were based on pedagogical approaches of teaching science, students’ motivation in learning sciences and challenges hindering effectiveness of teaching sciences. The paper contributes to policy makers and science teachers to employ appropriate strategies and integrate suitable technologies for teaching science in secondary schools. Based on the content analysis, tables are provided to summarise the research trend and findings. It has been found that the trend of low interest in learning science is still apparent for the past five years. The barriers of effective teaching and motivation have been the main discussion among researchers. Recommendations have been drawn to ensure teachers to involve in action research for effective intervention in teaching and learning science in schools. The limitations of study include the narrow search in the Google scholar rather than in indexed Scopus and ISI journals. Thus the quality of the research journals is not addressed.